Bacterial isolates and antibiotic susceptibility among women with abnormal vaginal discharge attending the gynecology clinic at a tertiary hospital in southwestern Uganda: a cross‑sectional study - Ahabwe, Onesmus Magezi; Kabanda, Taseera; Abesiga, Lenard; Mugisha, Julius; Kayondo, Musa; Ngonzi, Joseph; Tugume, Rodgers; Agaba, Collins David; Byamukama, Onesmus; Tibaijuka, Leevan; Lugobe, Henry Mark (BMC Women’s Health, 2023)
Background: Abnormal vaginal discharge is a common complaint among women of reproductive age, affecting about one- third of all women. In resource-limited settings where access to laboratory services is limited, treatment is usually syndromic. This approach may result in ineffective treatment, with high recurrence rates and a potential of developing antibiotic resistance. This study aimed to determine the bacterial isolates and antibiotic susceptibility among women with an abnormal vaginal discharge attending the gynecology clinic at a tertiary hospital in Southwestern Uganda. Methods: We conducted a hospital based cross-sectional study among 361 women aged 15–49 years, presenting with abnormal vaginal discharge at the gynecology clinic of Mbarara Regional Referral Hospital from December 2020 to June 2021. Demographic characteristics were collected using a structured questionnaire. We collected cervical and vaginal sterile swabs and subjected them to wet preparation and gram stain. The specimens were cultured for bacterial isolates. Susceptibility testing was performed on samples with bacterial isolates using the Kirby-Bauer disc diffusion method, on the commonly prescribed antibiotics in this setting. We summarized and described the bacterial isolates and antibiotic susceptibility patterns as frequencies and percentages. Results: We enrolled 361 women with abnormal vaginal discharge. Bacteria were isolated in 29.6% (107/361) of the women, and the commonest isolates included; Staphylococcus aureus 48.6% (52/107), Klebsiella pneumonia 29.9% (32/107) and Enterococcus faecalis 15% (16/107). Yeast cells were found in 17.7% (64/361) of the women with abnormal vaginal discharge. Cefuroxime (90.7%) and Ciprofloxacin (81.3%) had a high level of sensitivity while high levels of resistance were observed for Doxycycline (86.0%) and Azithromycin (67.0%). Conclusion: The common bacterial isolates were Staphylococcus aureus, Klebsiella pneumoniae and Enterococcus faecalis. The isolated bacteria were most sensitive to Cefuroxime and Ciprofloxacin but resistant to Doxycycline and Azithromycin. There is need for routine culture and susceptibility testing of women with abnormal vaginal discharge so as to guide treatment, minimize inappropriate antibiotic use and consequently reduce antibiotic resistance.
Keywords: Abnormal vaginal discharge; Antibiotic susceptibility; Bacterial isolates; Antimicrobial resistance; Mbarara